(untitled) (Clinics, 2007)
PURPOSE: To test the possibility of obtaining a practical and stable model of hyperinsulinemia and hyperglycemia in hamsters, substituting the drinking water by 10% or 20% fructose solutions for a period of 2, 4, or 6 months. METHODS: Male hamsters were divided into 3 main groups, further divided in 3 subgroups: Two months: Group Ia control (n = 51) received filtered water, Group Ib (n = 49) received 10% fructose solution instead of water, Group Ic (n=8) received 20% fructose solution instead of water. Four months: Group IIa control (n=8), Group IIb 10% fructose (n = 7), Group IIc 20% fructose (FIIc, n = 7). Six months: Group IIIa control (n = 6), Group IIIb 10% Fructose (n = 6), Group IIIc 20% Fructose (n = 5). All groups were fed with the same laboratory diet. The animals were weighed every 2 weeks during the study period. On the final day of each experiment (61st, 121st, and 181st day after the beginning of the study, respectively), the animals were weighed and anesthetized for blood collection to determine plasma glucose and insulin after at least a 12-h fast. Ten animals of group Ia and 10 of group Ib were evaluated to determine changes in macromolecular permeability induced by ischemia/reperfusion as measured in the cheek pouch microcirculation. RESULTS: Compared to controls, the animals that drank the 10% or 20% fructose solution had significantly greater weight gain (P < .001), fasting plasma glucose (P < .001) Reperfusion, after 30 min ischemia, resulted in an immediate but reversible increase in postcapillary leakage (L) of 89.0 ± 2.0 L/cm² (group Ia - controls), and 116.5 ± 4.8 L/cm² (group Ib 10% fructose), P < .001.These results suggest that chronic administration of either 10% or 20% fructose solutions could be used to experimentally induce a stable hamster model of hyperinsulinemia and hyperglycemia. CONCLUSION: The model might facilitate the study of basic mechanisms of hyperglycemia and hyperinsulinemia affecting the microvasculature as demonstrated by the findings regarding ischemia/reperfusion after only 2 months of treatment.